Adaptive minimum variance methods for direct blind multichannel equalization - Xu, Zhengyuan Daniel; Tsatsanis, Michail K. (Signal processing, 1999)
In this paper, stochastic gradient and RLS-based methods are presented for designing direct adaptive equalizers. Self-recovering solutions are obtained by minimizing the equalizer’s output variance subject to appropriate constraints. The constraints are chosen to guarantee no desired signal cancellation and are also jointlyand adaptively optimized to improve performance. The resulting algorithm may be interpreted as an optimal version of earlier linear prediction-based approaches. It is shown that the algorithm enjoys global convergence. Moreover, the constraint parameters converge to the channel parameters at high SNR. Comparisons with other blind and trained methods are presented. In diesem Beitrag stellen wir “stochastic gradient”- und RLS-basierte Verfahren zur adaptiven direkten Entzerrung vor. Wir präsentieren “self-recovering” Lösungen, die man durch eine Minimierung der Varianz des Entzerrerausgangs unter geeigneten Nebenbedingungen erhält. Die Nebenbedingungen sind derart gewählt, daß keine Nutzsignalanteile entfernt werden. Weiters werden diese Nebenbedingungen gemeinsam adaptiv optimiert, so daß es zu einer Verbesserung der Performance des Entzerrers kommt. Der vorgestellte Algorithmus kann als eine optimale Version von früheren auf linearer Prädiktion basierenden Verfahren interpretiert werden. Wir zeigen, daß der Algorithmus globale Konvergenz aufweist. Bei großem SNR konvergieren die in die Nebenbedingungen eingehenden Parameter gegen die Kanalparameter. Schließlich werden Vergleiche mit anderen blinden Verfahren und Verfahren basierend auf Referenzdaten gezeit. Dans cet article, on présente des méthodes basées sur le gradient stochastique ou sur les moindres carrés récursifs (RLS) pour la construction d’égaliseurs adaptatifs. Des solutions autodidactes sont obtenues en minimisant sous les contraintes appropriées la variance en sortie de l’égaliseur. Les contraintes sont choisies pour éviter l’annulation du signal désiré, et sont conjointement et adaptativement optimisées pour améliorer les performances. L’algorithme résultant peut être interprété comme une version optimale d’approches antérieures de type prédiction linéaire. On montre que l’algorithme converge globalement. En outre, les paramètres de contrainte convergent vers les paramètres du canal à fort SNR. Des comparaisons avec d’autres méthodes aveugles ou informées sont présentées.